Pengaruh Literasi Keuangan dan Pengendalian Diri Terhadap Manajemen Keuangan Pribadi Masyarakat Penerima BLT Lembang Bululangkan Toraja Utara - Grace Sriati Mengga; Dian Intan Tangkeallo; Rice Bakkula (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The purpose of this study was to determine the effect of financial literacy and self-control on personal financial management. This type of research is descriptive quantitative. The type of data used is primary data, namely data obtained directly from the public through filling out questionnaires and secondary data, namely data obtained from various sources in the form of notes, books, and journals related to research problems. The results of the study partially show that financial literacy has a positive and significant effect on personal financial management, self-control has a positive and significant effect on personal financial management. Through simultaneous tests it was found that financial literacy and self-control simultaneously had a positive and significant effect on personal financial management.